Biodegradable collagen sponge reinforced with chitosan/calcium pyrophosphate nanoflowers for rapid hemostasis. (15th August 2017) - Yan, Tingsheng; Cheng, Feng; Wei, Xinjing; Huang, Yudong; He, Jinmei
Graphical abstract: The preparation process of chitosan nanoparticle collagen sponge and its hemostatic evaluation. Highlights: A chitosan/calcium pyrophosphate nanoflowers coating collagen sponge was designed. The sponge could promote the blood clotting and achieve hemorrhage control. The sponge can degrade in 3 weeks thus suitable for post-operative treatment. Abstract: Efficient and biodegradable hemostatic materials become increasingly important in civilian and military clinical. However, traditional hemostatic materials are difficult to achieve expected effects especially in parenchymal organs with rich vascularity. In facing these challenges, we designed a biodegradable collagen sponge reinforced with chitosan/calcium pyrophosphate nanoflowers (CPNFs-Col sponge) for rapid hemostasis. With specific performances, such as rapid water absorption ability, the positive surface rich in amino groups and high specific surface area (952.5 m 2  g −1 ), the obtained CNPFs-Col sponge with optimized composition could activate the intrinsic pathway of coagulation cascade, induce haemocytes and platelets adherence, promote the blood clotting and achieve hemorrhage control in vitro and in vivo. In addition, the CNPFs-Col sponge can be completely biodegraded in 3 weeks, which is suitable for post-operative treatment and peritoneal adhesion prevention. It can be concluded that the CPNFs-Col sponge would become a promising candidate for clinical hemostatic applications.